Mutations in hik26 and slr1916 lead to high-light stress tolerance in Synechocystis sp. PCC6803 - Katsunori Yoshikawa (Nature Portfolio, 2021)
In this paper, the authors investigated the high light stress response in Synechocystis sp. PCC6803 and revealed two key mutations in hik26 and slr1916 using whole genome sequencing and reverse engineering. Here, the high light tolerant strain exhibited no growth inhibition in conditions up to 9000 μmol m−2 s−1, which had no effect on excitation-energy flow and instead showed an increase in isiA expression.